Cooling during transportation of newborns with hypoxic ischemic encephalopathy using phase change material mattresses in low-resource settings: a randomized controlled trial in Hanoi, Vietnam - Hang. T. T. Tran; Dien. M. Tran; Ha. T. Le; Lena Hellström-Westas; Tobias Alfvén; Linus Olson (BMC, 2024)
Abstract Objective To determine the effectiveness of phase-change-material mattress (PCM) during transportation of newborns with hypoxic ischemic encephalopathy (HIE). Study design Randomized controlled trial of newborns with HIE from June 2016 to December 2019. Patients were randomized to transport with PCM or without PCM (control) when transferred to a cooling center in northern Vietnam. Primary outcome measure was mortality rate, secondary outcomes including temperature control and adverse effects. Result Fifty-Two patients in PCM-group and 61 in control group. Median rectal temperature upon arrival was 34.5 °C (IQR 33.5-34.8) in PCM-group and 35.1 °C (IQR 34.5-35.9) in control group (p = 0.023). Median time from birth to reach target temperature was 5.0 ± 1.4 h and 5.5 ± 1.2 h in the respective groups (p = 0.065). 81% of those transported with PCM versus 62% of infants transported without (p = 0.049) had reached target temperature within the 6-h timeframe. There was no record of overcooling (< 32 °C) in any of the groups. The was no difference in mortality rate between the two groups (33% and 34% respectively (p > 0.05)). Conclusion Phase-change-material can be used as a safe and effective cooling method during transportation of newborns with HIE in low-resource settings. Trial registration The study was retro-prospectively registered in Clinical Trials (04/05/2022, NCT05361473).